Evaluation of Cadmium Absorption by Pepper Capsicum Annuum involving Microwave Induced Plasma Atomic Emission Spectrometry (MIP-AES) - Filho, Alexandre R. S.; Silva, Priscila P.; Lima, Alexandre F.; Alves, Evandro R. (Seven Editora, 2023)
Contamination by toxic metals in vegetables destined for consumption has been caused recurrent concerns due to the cumulative effect on the human body, resulting in risks to health. The aim of this work was to evaluate the absorption of cadmium by roots and fruits of green and red square peppers cultivated in solutions 0.00; 5.00; 10.00 and 15.00 mg L-1 CdCl2.2H2O (cadmium chloride dihydrate p.a.). Microwave induced plasma atomic emission spectrometry (MIP-AES) was employed for the cadmium quantification in the samples. The results of cadmium absorption by the roots and fruits of the red square pepper were 0.00; 0.25; 1.50 and 1.99 and 0.00; 0.00; 0.08; 0.19 mg L-1 and for green pepper, 0.00; 0.33; 1.67 and 1.99 mg L-1 and 0.00; 0.00; 0.09 and 0.17 mg L-1, respectively. The increase in the concentration of contaminant solutions applied to the soil resulted in higher rates of cadmium absorption by the roots in relation to the fruits of both pepper varieties. The results were promising, according to the proposed curves and adjustments (0.87 > R > 1.0), generating predictability in the ranges of concentrations evaluated. DOI:https://doi.org/10.56238/interdiinovationscrese-061